2005
DOI: 10.2320/matertrans.46.2838
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modeling of the Undercooled Liquid in the Ni–Zr System

Abstract: Using thermodynamic data obtained over a wide range of temperatures, a thermodynamic assessment of the Ni-Zr system was carried out. The associated solution model was applied to describe the short range ordering in the liquid, and the glass transition was treated as a second order transition, using the Hillert-Jarl functions. The driving force of crystallization, and the time-temperature-transformation (TTT) curves were estimated from the optimized parameter set, and compared with experimental data and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…Using those thermodynamic databases, several attempts have been made to estimate the GFA such as the driving force for crystallization from the undercooled liquid, and the critical cooling rate for the amorphous formation [5][6][7]. Recently, the authors have shown in the Cu-Zr binary systems [8] that those thermodynamic properties at low temperatures, which are missing in previous assessments of those binary systems [9][10][11], are indispensable for accurate estimation of the driving forces and the critical cooling rates.…”
Section: Introductionmentioning
confidence: 98%
“…Using those thermodynamic databases, several attempts have been made to estimate the GFA such as the driving force for crystallization from the undercooled liquid, and the critical cooling rate for the amorphous formation [5][6][7]. Recently, the authors have shown in the Cu-Zr binary systems [8] that those thermodynamic properties at low temperatures, which are missing in previous assessments of those binary systems [9][10][11], are indispensable for accurate estimation of the driving forces and the critical cooling rates.…”
Section: Introductionmentioning
confidence: 98%
“…Nickel and copper are neighbours in the periodic table and have many similarities; for example, they both have the face-centred cubic (cubic close-packed) crystal structure, very similar densities, atomic sizes, and electronegativities [1]. Upon alloying with zirconium, nickel forms eight and copper forms six stable intermetallic compounds with complicated crystal structures, giving complex Ni-Zr [2] and Cu-Zr structural models for Cu-Zr glasses and found that they are composed of interconnected clusters with icosahedral and dodecahedral symmetry. Mattern et al [31] studied Cu-Zr glasses by reverse Monte-Carlo (RMC) simulation and analysed the model configurations.…”
Section: Introductionmentioning
confidence: 99%
“…[17].The discrepanciesbetween the calculated and the measured are above5 0 8 C.Though the eutectictemperature,a bout 1003 8 C, calculated byAbee tal. [18]seemsclosetothe measured data, the calculated melting points of NiZrand NiZr 2 aremuchlowerthanthe experimentaldata.Thoseresearchers [14 -17]questionedthe experimentalwork [6], becausetheynoticed thatt he measured liquidus [6]of the NiZr 2 phaseisextremelyasymmetricand abnormallysteep on the Niside,whichi st hermodynamicallyimprobable [19].Considering the discrepancybetween the calculations and the measurements,the eutectictemperaturebetween the NiZrand NiZr 2 compoundswasdetermined experimentallyin the presentwork.…”
Section: Introductionmentioning
confidence: 98%
“…[17]and Abeetal. [18]assessed the Ni-Zrsystem thermodynamicallyu sing the CALPHAD method,a nd obtained fivesets of optimized thermodynamicparameters fort his system.The biggest differencebetween the assessed [14 -18]phasediagramsand the experimentalones [6]isthe eutectictemperaturebetween the NiZrand NiZr 2 compounds. The experimentallymeasured temperaturewas1010 8 Cby Kirkpatrickand Larsen [6], while the calculated wasabout 1060 8 CbySaunders [14], 1065 8 CbyGhosh [15], 1111 8 C byYuand Jin [16]and 1078 8 CbyZaitsevetal.…”
Section: Introductionmentioning
confidence: 99%